Self-excited vibrations of spring-loaded valves operating at small pressure drops. (November 2018) - El Bouzidi, Salim; Hassan, Marwan; Ziada, Samir
Abstract: Flow-induced vibration is a major issue for spring-loaded valves. However, their complex geometry, combined with their diversity of operational conditions, creates a significant challenge for modelling their dynamic response to potential excitation mechanisms. This paper proposes an analytical framework to describe flow–sound–structurecoupling in spring-loaded valves operating at subcritical conditions, therefore without the occurrence of choking at the vena contracta . The model consists of a single-degree of freedom model of the valve structure, a pseudo-force implicit algorithm to calculate impact forces, a one-dimensional unsteady Bernoulli model to describe the flow, and a one-dimensional wave propagation finite difference scheme to account for the acoustic feedback. The model has shown excellent agreement with experimental results as well as promising predictive capabilities for valve life and wear assessment. Highlights: A non-linear reduced-order model is proposed to describe flow–sound–structure interaction in spring-loaded valves. The acoustic feedback is essential to the onset of instability. The model has shown excellent agreement with experimental data. The model's time domain formulation can be used to predict valve fatigue and wear.